2016
DOI: 10.17140/poj-1-106
|View full text |Cite
|
Sign up to set email alerts
|

The Enigma of Type 3c Diabetes in Chronic Pancreatitis

Abstract: Pancreatogenic or Type 3c diabetes (T3cDM) is relatively a new entry in the complex world of diabetes study. While the general population and physicians are well aware of type 1 and type 2 diabetes mellitus, as evidenced by numerous study groups and the reams of guidelines on diagnosis and treatment of type 1 and type 2 diabetes mellitus, relatively much less is known, considered and documented about diabetes mellitus that occurs secondary to pancreatic diseases. A casual search of Pubmed reveals less than 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Diabetes develops in CP mostly as a result of pancreatic inflammation destroying islet cells. Malnutrition also impairs incretin production, leading to decreased insulin production from the surviving β cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes develops in CP mostly as a result of pancreatic inflammation destroying islet cells. Malnutrition also impairs incretin production, leading to decreased insulin production from the surviving β cells [40].…”
Section: Discussionmentioning
confidence: 99%
“…[ 7 ] On the other side, it has been observed that 38% of patients suffering from CP develop diabetes within the next 1–2 years. [ 8 ] Hence, it becomes essential to diagnose cases of CP at the earliest to alter the natural course of the disease. However, biochemical studies are not helpful in definitive diagnosis during early stages.…”
Section: Discussionmentioning
confidence: 99%
“…While early and periodic screening for DM with CP is recommended, the same is also critical for non-diabetic patients with CP as they are strongly predisposed to T3cDM [6]. Patients diagnosed with CP without DM exhibit an extended glucose tolerance curve, and once diagnosed with CP, 40% of patients exhibit early-onset DM [108]. Another study also showed that a two-hour oral glucose tolerance test helped in early detection of glycemic alteration even when fasting blood glucose and HbA1c were normal, indicating that an appropriate management could help prevent CP severity [109].…”
Section: Managementmentioning
confidence: 99%